2017
DOI: 10.1074/jbc.m116.772020
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein exhibits altered turnover kinetics in a mouse model of Alexander disease

Abstract: Edited by George N. DeMartinoMutations in the astrocyte-specific intermediate filament glial fibrillary acidic protein (GFAP) lead to the rare and fatal disorder, Alexander disease (AxD). A prominent feature of the disease is aberrant accumulation of GFAP. It has been proposed that this accumulation occurs because of an increase in gene transcription coupled with impaired proteasomal degradation, yet this hypothesis remains untested. We therefore sought to directly investigate GFAP turnover in a mouse model of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…In contrast, the half‐life of GFAP in mutant mice in vivo was much shorter than in control mice (∼ 15 days vs. 28 days, respectively). The faster turnover of GFAP in mutant mice in vivo , as the authors propose, may be because of an acceleration of both protein synthesis and protein degradation . It should be noted that the analysis of proteins in vivo was performed at 2 months of age, when astrocytes have already accumulated high levels of GFAP and many RFs.…”
Section: Murine Models Of Axdmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast, the half‐life of GFAP in mutant mice in vivo was much shorter than in control mice (∼ 15 days vs. 28 days, respectively). The faster turnover of GFAP in mutant mice in vivo , as the authors propose, may be because of an acceleration of both protein synthesis and protein degradation . It should be noted that the analysis of proteins in vivo was performed at 2 months of age, when astrocytes have already accumulated high levels of GFAP and many RFs.…”
Section: Murine Models Of Axdmentioning
confidence: 92%
“…Another contributing factor to GFAP protein levels is the turnover rate of the protein. In an interesting study of protein turnover, that of GFAP in the AxD KI mice in vivo and in primary astrocyte cultures from these mice was compared to GFAP turnover in control mice . The half‐life of GFAP protein in vitro was much shorter than in vivo and did not differ between KI and control astrocytes.…”
Section: Murine Models Of Axdmentioning
confidence: 99%
“…Yet at the same time there is an increase in autophagy ( Tang et al., 2008 ) and activation of caspases 3 and 6 ( Chen et al., 2011 , 2013 ). When the knockin mouse model was studied during adulthood using methods of isotope turnover, the half-life of GFAP was observed to be actually decreased ( Moody et al., 2017 ). Furthermore, recent studies on autopsy tissues from three patients found that the mutant form of the protein is not the majority of the GFAP present in the brain, suggesting that it is less stable than the wild type ( Heaven et al., 2019 ).…”
Section: Dangermentioning
confidence: 99%
“…Alexander disease is a rare, fatal neurologic disorder characterized by white‐matter degeneration and cytoplasmic inclusions in astrocytes known as Rosenthal fibers, a product of heterozygous mutations in the GFAP gene (Moody, Barrett‐Wilt, Sussman, & Messing, ). The cytoplasmic accumulations of GFAP and Rosenthal fibers in astrocytes cause proteasome inhibition, stress kinase activation, mechanistic target of rapamycin activation, loss of glutamate‐ and potassium‐buffering capacity, loss of astrocyte coupling, and changes in cell morphology (Olabarria & Goldman, ).…”
Section: Gfap and Neurological Diseasesmentioning
confidence: 99%